If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y/15+6=y/6+12
We simplify the equation to the form, which is simple to understand
y/15+6=y/6+12
Simplifying:
+ 0.0666666666667y+6=y/6+12
Simplifying:
+ 0.0666666666667y+6=0.166666666667y+12
We move all terms containing y to the left and all other terms to the right.
+ 0.0666666666667y-0.166666666667y=+12-6
We simplify left and right side of the equation.
-0.1y=+6
We divide both sides of the equation by -0.1 to get y.
y=-59.9999999998
| -9=-6+3x | | 16x^4=y^2 | | 0=2(3x-5)+8(4x+7) | | -16t^2+3t+1.3=h(t) | | 12+m/4=3d-1/2 | | (2x-3)(x+3)=3 | | 4(a+3)=6(a-(5-a)) | | 6(3+v)+36v=13v | | 7r-8r=6 | | 5xy-3y-4=0 | | X-3/5+3/5=-x/2 | | -5t-26=18t | | -(100/-4) | | 3x+9=15forx | | 0=16t^2+44t-24 | | -3/4+7/3 | | 4=2a+37 | | 4x^2=12x-8 | | -4x^2-40x-106=0 | | -17=1+4n-7n | | g(x)=2f(x) | | -4/3-1 | | 6y+4=3(2y-10) | | 4/3-1 | | 2b-7b=5 | | 8x^2-13x-6x=0 | | x-ba=c+da | | a-bx=c+dx | | x+2(x+1)=122-3(x+2) | | -8(m+1)-m-12=-9(m+4)+16 | | x+(x-3)=9 | | -8=m/6-9 |